This Voice Has Come for Your Sake: Seeing and Hearing in John’s Gospel - Setzer, Claudia (Journal for religion, film and media, 2016)
The gospel of John confronts the problems of human finitude and separation from God and others. Its theological innovations push at the boundaries of time and space, invoking the senses as vehicles for healing separation. The act of hearing is particularly significant and draws on biblical and rabbinic concepts. Perception, couched in the sense organs, is the source of understanding God. Philosophers Gilles Deleuze and Henri Bergson consider the role of sense-perception in understanding the self in relation. Transhumanism promotes the extension of sense-capabilities of hearing and seeing. Enhancement of the senses allows greater capacity for the self to develop, reduces alienation, and provides the possibility, in secular terms, of what John promised in religious terms, “more abundant life” (John 10:10).